Effects of potassium dichromate on the survival and reproduction of Moina micrura Kurz. 1875 (Cladocera: Moinidae) - Mau, Trinh Dang; Trang, Le Vu Khanh; Trinh, Nguyen Nhung Thuy; Son, Tran Ngoc; Minh, Vo Van (Academia Journal of Biology, 2019)
Today, heavy metal pollution is an urgent problem in the world including Vietnam. An analytical approach is very important to identify, assess and forecast environmental risks from toxic components, in which ecotoxicology is considered to be the optimal tool. We conducted a study on M. micrura in order to contribute the creation of a biological basis for the use of zooplankton as an early warning of the risk of water pollution. The results showed that M. micrura was isolated from 29/3 Park Lake, Da Nang City, central Vietnam. The acute toxicity test of potassium dichromate on M. micrura showed LC 50 at 12, 24 and 48 hr were 0.26, 0.15 and 0.08 mg.l-1 K2Cr2O7, respectively. EC 50 was 0.015 mg.l-1 K2Cr2O7 for egg parameter and 0.009 mg.l-1 K2Cr2O7for neonate parameter. The results of acute and chronic toxicity tests showed that M. micrura was more sensitive than D. magna, D. pulex and C. cornuta.